Developing Handouts Accompanied by Practice Questions on Inheritance Material for SMP/MTs - Megahati S, Ruth Rize Paas; Elfina, Yuci (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
To make it easier to present the material, one of the materials that can be developed is a handout. This research aims to produce handouts accompanied by practice questions on inheritance material for class IX SMP/MTs. This research was conducted at MTsN Lembah Gumanti in March of the 2014/2015 academic year. This research includes development research, namely the development of handouts accompanied by practice questions with modified 4-D models consisting of the define, design, and developing stages. The data is in the form of primary data, consisting of scores from filling out validity and practicality questionnaires by teachers and students. The data were analyzed using descriptive analysis in the form of percentages. The handouts produced were categorized as very valid, both in the didactic, construction, and technical categories, with a handout validity value of 89.10%. The resulting handout was categorized as very practical according to the teacher with a score of 89.30%, and according to students with a score of 89.6%, it was categorized as very practical. So, it can be concluded that this research has produced handouts accompanied by practice questions that are very valid and very practical so they are suitable for use in the learning process.